Engineering bioinks for Bio 3D printing - Decante, G. (2021)
In recent years, three-dimensional (3D) bioprinting has attracted wide research interest in biomedical engineering and clinical applications. This technology allows for unparalleled architecture control, adaptability and repeatability that can overcome the limits of conventional biofabrication techniques. Along with the emergence of a variety of 3D Bioprinting methods, bioinks have also come a long way. From their first developments to support bioprinting requirements, they are now engineered to specific injury sites requirements to mimic native tissue characteristics and to support biofunctionality. Current strategies involve the use of bioinks loaded with cells and biomolecules of interest, without altering their functions, to deliver in situ the elements required to enhance healing/regeneration. The current research and trends in bioink development for 3D Bioprinting purposes is overviewed herein.